Mapping Correlates of Career Choice among Administrative Science Undergraduates: Insights from Social Cognitive Career Theory - Mayowan, Yuniadi (Dinasti International Journal of Management Science, 2025)
Understanding why undergraduates commit to particular career paths informs curriculum design and career-guidance services in higher education. Guided by Social Cognitive Career Theory, this study explores the relationships among learning experiences, self-efficacy, outcome expectations, career interest, and career choice among 140 students in the Faculty of Administrative Science, Universitas Brawijaya. A validated five-part questionnaire captured perceptions on each construct, and Pearson correlations were computed to map their interconnections. Results show strong positive associations between career choice and career interest (r = 0.79), outcome expectations (r = 0.72), and self-efficacy (r = 0.68), while learning experiences correlate moderately with the other variables. The pattern suggests that cultivating engaging experiences that enhance efficacy beliefs and clarify expected outcomes can foster deeper interests, thereby aligning students’ eventual choices with institutional learning goals. Findings offer evidence to refine competency-based curricula and develop focused career-mentoring initiatives that bridge academic programmes with evolving labour-market demands.